Analisis Green Marketing Tools terhadap Purchase Behaviour dengan Mediasi Purchase Intention pada Konsumen Milenial di Jakarta - Windy Eka Saputri; Anas Lutfi (Universitas Tarumanagara, 2021)
This study aims to explain green marketing tools that influence purchase intention and purchase behavior in Jakarta to purchase Ades. The instrument of this research is a questionnaire distributed to 522 millennials in Jakarta. Data collected was analyzed using SmartPLS analysis. The results of this study indicate that there is an influence of ecolabel, ecobrand, environmental advertisement on purchase intention. In addition, there is an influence on purchase intention and purchase behavior. Furthermore, the results of the study indicate that purchase intention mediates the relationship between ecobrand and environmental advertisement towards purchase behavior. Penelitian ini bertujuan untuk menjelaskan green marketing tools yang purchase intention dan purchase behaviour di Jakarta pada pembelian Ades. Instrumen penelitian ini berupa kuesioner yang disebarkan kepada 522 milenial di Jakarta. Data yang terkumpul dianalisis menggunakan SmartPLS. Hasil penelitian ini menunjukkan bahwa terdapat pengaruh eco-label, eco-brand, dan environment advertisement terhadap purchase intention. Selain itu terdapat pengaruh purchase intention dan purchase behaviour. Hasil penelitian menunjukkan bahwa purchase intention memediasi hubungan antara eco-brand dan environmental advertisement terhadap purchase behaviour.